Evaluating the temporal trend of completed suicides referred to the Iranian Forensic Medicine Organization during 2006–2010. (April 2016) - Shojaei, Ahmad; Moradi, Saadolah; Alaeddini, Farshid; Khodadoost, Mahmood; Abdizadeh, Abdolraoof; Khademi, Ali
Abstract: Objective: The objective of the present study was to determine the temporal trend of the rate of completed suicides in Iran during 2006–2010. Material and methods: Data on completed suicides were collected from the national suicide registry of the Iranian Forensic Medicine Organization. The rates were calculated for males and females for each year of the study period, from which the temporal trends were determined. Statistical analyses were conducted using SPSS software, using chi-squared and analysis of variance (ANOVA) tests. Results: The overall rate of suicide was 4.7/100, 000, with a male/female ratio of 2.4. The mean age of suicide was 31.9 years, which was significantly higher in males. Hanging was the most common method, followed by poisoning and self-immolation. During the study period, the rate of drug poisoning almost doubled, while that of firearms halved. The rates of hanging and self-immolation also increased in the last years of the study period. Conclusion: According to the results of this study, it can be concluded that Iran has had a constant rate of completed suicides over the past decade. Our study also indicated the need for future nationwide studies on the risk factors of suicidal behavior and on different suicide methods in the entire Iranian population. Highlights: We assessed the temporal trend of the rate of completed suicides in Iran during the period 2006–2010. Data were collected from the national suicide registry of the Iranian Forensic Medicine Organization. The overall rate of suicide was 4.7/100, 000, with a male/female ratio of 2.4. Hanging was the most common method of suicide, followed by poisoning and self-immolation. It can be concluded that Iran has witnessed a constant rate of completed suicides over the past decade.